Cross-Border Mergers as Instruments of Comparative Advantage - J. Peter Neary (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
A two-country model of oligopoly in general equilibrium is used to show how changes in market structure accompany the process of trade and capital market liberalisation. The model predicts that bilateral mergers in which low-cost firms buy out higher-cost foreign rivals are profitable under Cournot competition. With symmetric countries, welfare may rise or fall, though the distribution of income always shifts towards profits. The model implies that trade liberalisation can trigger international merger waves, in the process encouraging countries to specialise and trade more in accordance with comparative advantage.
Keywords: L13; F12; F10; 330; Comparative advantage; cross-border mergers; GOLE (General Oligopolistic Equilibrium); market integration; merger waves; Übernahme; Grenze; Oligopol; Zwei-Länder-Modell; Aussenhandelsliberalisierung; Kapitalmarktliberalisierung; Komparativer Kostenvorteil